Specialist training in Fiji: Why do graduates migrate, and why do they remain? A qualitative study - Usher Kim; Moulds Robert; Oman Kimberly M (BMC, 2009)
Abstract Background Specialist training was established in the late 1990s at the Fiji School of Medicine. Losses of graduates to overseas migration and to the local private sector prompted us to explore the reasons for these losses from the Fiji public workforce. Methods Data were collected on the whereabouts and highest educational attainments of the 66 Fiji doctors who had undertaken specialist training to at least the diploma level between 1997 and 2004. Semistructured interviews focusing on career decisions were carried out with 36 of these doctors, who were purposively sampled to include overseas migrants, temporary overseas trainees, local private practitioners and public sector doctors. Results 120 doctors undertook specialist training to at least the diploma level between 1997 and 2004; 66 of the graduates were Fiji citizens or permanent residents; 54 originated from other countries in the region. Among Fiji graduates, 42 completed a diploma and 24 had either completed (21) or were enrolled (3) in a master's programme. Thirty-two (48.5%) were working in the public sectors, four (6.0%) were temporarily training overseas, 30.3% had migrated overseas and the remainder were mostly in local private practice. Indo-Fijian ethnicity and non-completion of full specialist training were associated with lower retention in the public sectors, while gender had little impact. Decisions to leave the public sectors were complex, with concerns about political instability and family welfare predominating for overseas migrants, while working conditions not conducive to family life or frustrations with career progression predominated for local private practitioners. Doctors remaining in the public sectors reported many satisfying aspects to their work despite frustrations, though 40% had seriously considered resigning from the public service and 60% were unhappy with their career progression. Conclusion Overall, this study provides some support for the view that local or regional postgraduate training may increase retention of doctors. Attention to career pathways and other sources of frustration, in addition to encouragement to complete training, should increase the likelihood of such programmes' reaching their full potentials.